Analysis of the Application of Quizwhizzer in Social Natural Sciences Learning at Madrasah Ibtidaiyah - Zidane, Mokhammad Rizqi; Prastowo, Andi (Pascasarjana Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga, 2024)
Teachers as the most important source of transmitting learning material undoubtedly have thousands of heads to achieve competent teaching quality. In this current era, teachers must be able to change learning media that are allegedly monotonous and can make students bored in class into media that are innovative and make students enthusiastic in class. Technology and information-based learning environments are used in the learning process or in learning strategies. Quizwhizzer. is a learning media that helps students learn independently, can be used anytime and anywhere, and is very useful for learning activities. Additionally Quizwhizzer. able to open students' knowledge because of Quizwhizzer. is very open and contains a lot of interactive learning, so that it can enable students to get lessons that may not have been taught in class. The aim of this research is to reveal the use of Quizwhizzer. in learning activities. This research is a qualitative descriptive study. Data was collected through observation and interviews. Data analysis was carried out through transcription, coding and verification. The research results show that teachers use Quizwhizzer in class. This media makes it easier for teachers to provide educational material to students through the interactive game Quizwhizzer.